The efficacy of platelet-rich plasma applicated in spinal fusion surgery: A meta-analysis - Yu, Hongwei; Zhou, Zhaohong; Yu, Bin; Sun, Tianwei; Tang, Qiong; Jia, Yutao (Frontiers in Surgery, 2022)
Objective: The purpose of this meta-analysis is to evaluate the effect of the application of platelet-rich plasma (PRP) in spinal fusion surgery on the fusion rate of the spine. Methods: A comprehensive search of the PubMed, Embase, Cochrane Library, and Science Direct databases was conducted to identify randomized control trials (RCTs) or observational cohort studies that evaluated the efficacy and safety of PRP in spinal fusion. Data on final fusion rate, revision surgery rate due to non-fusion, changes in the visual analogue scale (VAS), estimated blood loss (EBL), operative time were collected from the eligible studies for meta-analysis. Patients were divided into PRP and non-PRP groups according to whether PRP was used at the spinal fusion procedure. Results: According to the selection criteria, 4 randomized controlled trials and 8 cohort studies with 833 patients and 918 levels were included. Compared with the non-PRP group, group PRP showed a lower fusion rate and the difference was statistically significant (OR=0.66, 95% CI:(0.46,0.95), P=0.02); At the same time, a higher percentage of the PRP group underwent revision surgery due to nonfusion than the non-PRP group, and the difference was statistically significant(OR=2.86, 95% CI:(1.10,7.42), P=0.03).The PRP and non-PRP groups showed no significant differences in VAS changes (WMD=0.36, 95% CI:(-0.37,1.09), P=0.33); Application of PRP does not reduce the estimated blood loss(WMD=-86.03, 95% CI:(-188.23,16.17), P=0.10). In terms of operation time, using PRP does not prolong operation time(WMD=-3.74, 95% CI:(-20.53,13.04),P=0.66). Conclusion: Although a promising and safe bone graft extender, PRP is not yet ready for clinical application, conversely, the application of PRP may reduce the rate of spinal fusion.